2013
DOI: 10.1093/cercor/bht067
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy-Induced Motility of Differentiated Neurons

Abstract: Neuronal ectopia, such as granule cell dispersion (GCD) in temporal lobe epilepsy (TLE), has been assumed to result from a migration defect during development. Indeed, recent studies reported that aberrant migration of neonatal-generated dentate granule cells (GCs) increased the risk to develop epilepsy later in life. On the contrary, in the present study, we show that fully differentiated GCs become motile following the induction of epileptiform activity, resulting in GCD. Hippocampal slice cultures from tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 68 publications
7
43
0
Order By: Relevance
“…Supplementation with Reelin can prevent granule cell dispersion following kainic acid injection (54). We found that complete loss of Reelin in adult mice resulted in no dispersion of the granule cell layer, suggesting that additional signaling cascades are activated in response to enhanced glutamate release in MTLE and experimental kainate application, respectively, eventually leading to increased granule cell motility and dispersion (55). …”
Section: Discussionmentioning
confidence: 99%
“…Supplementation with Reelin can prevent granule cell dispersion following kainic acid injection (54). We found that complete loss of Reelin in adult mice resulted in no dispersion of the granule cell layer, suggesting that additional signaling cascades are activated in response to enhanced glutamate release in MTLE and experimental kainate application, respectively, eventually leading to increased granule cell motility and dispersion (55). …”
Section: Discussionmentioning
confidence: 99%
“…8). Pronounced migration of newborn granule cells into the molecular layer following Disc1 KO or KD suggest a similar phenomenon could be occurring in these animals [136138]. Finally, reduced Disc1 expression is correlated with expansion of the granule cell layer in the kindling model of epilepsy [139, 140], supporting the hypothesis that changes in Disc1 expression may mediate some of the granule cell abnormalities observed in epilepsy.…”
Section: Adult Neurogenesis Is a Common Target Of Genes Linked To mentioning
confidence: 91%
“…In human patients with MTLE, a negative correlation was found between granule cell dispersion and the expression of reelin RNA [8,10,12,14,86,100]. In animal models, this hypothesis was confirmed in both ex vivo slice culture infused with kainate [20,99] and the KA-MTLE mouse model [14,24,26,27,101,102]. Two different mechanisms were suggested to explain the decrease in reelin expression:…”
Section: Granule Cell Dispersionmentioning
confidence: 83%
“…Moreover, the application of kainate in slice culture induced a cell bodies translocation of fully mature granule cells and changed their dendritic organization [20,85]. The fact that in the Reeler mouse mutant where the protein reelin is lacking [99][100][101]111], GCD is observed, suggested that this protein plays a key role in the control of granule cell migration during brain development [100,112].…”
Section: Granule Cell Dispersionmentioning
confidence: 99%
See 1 more Smart Citation